Penerapan Etika Komunikasi Interpersonal dalam Menghadapi Hubungan Toxic di Kalangan Gen Z - Nandayarni, Ivo; Khairunnisa, Afifah Zahrah; Narima, Puput Ulfi; Rahma, Syifa Amira; Azzahra, Adinda Hilda; Pratama, Fikri Arvandra (Universitas Merdeka Malang, 2024)
The purpose of the study was to describe the application of interpersonal communication ethics in unhealthy relationships. This study was descriptive qualitative with observation, documentation and interview methods involving 22 informants. The criteria for informants were experiencing unhealthy relationships. Data analysis techniques included data reduction, data presentation and drawing conclusions. The results showed that informants was afraid and trauma in reconnecting with the opposite sex and chose to cut off communication from unhealthy relationships. The feelings they had included being isolated, restricted, and controlled by their partners. Forms of violence in relationships are not only physical, but can also be verbal, emotional, and psychological violence.